Dark Atoms and the Positron-Annihilation-Line Excess in the Galactic Bulge - J.-R. Cudell; M. Yu. Khlopov; Q. Wallemacq (Advances in High Energy Physics)
It was recently proposed that stable particles of charge −2, O--, can exist and constitute dark matter after they bind with primordial helium in O-helium (OHe) atoms. We study here in detail the possibility that this model provides an explanation for the excess of gamma radiation in the positron-annihilation line from the galactic bulge observed by INTEGRAL. This explanation assumes that OHe, excited to a 2s state through collisions in the central part of the Galaxy, deexcites to its ground state via an E0 transition, emitting an electron-positron pair. The cross-section for OHe collisions with excitation to 2s level is calculated and it is shown that the rate of such excitations in the galactic bulge strongly depends not only on the mass of O-helium, which is determined by the mass of O--, but also on the density and velocity distribution of dark matter. Given the astrophysical uncertainties on these distributions, this mechanism constrains the O-- mass to lie in two possible regions. One of these is reachable in the experimental searches for stable multicharged particles at the LHC.